A Preliminary Study of an Internet‐Based Intervention for OEF/OIF Veterans Presenting for VA Specialty PTSD Care. Issue 2 (April 2015) - Belsher, Bradley E.; Kuhn, Eric; Maron, David; Prins, Annabel; Cueva, David; Fast, Elsbeth; France, Deborah
<x xml:space="preserve">Abstract</x> This preliminary study sought to evaluate the feasibility and potential effectiveness of a cognitive–behavioral, web‐based intervention for posttraumatic stress in Operation Enduring Freedom/Operation Iraqi Freedom (OEF/OIF) veterans who are not able to participate, or not eligible to participate, in evidence‐based posttraumatic stress disorder (PTSD) treatments. The study used an uncontrolled pre‐posttest design with a sample of 24 OEF/OIF veterans presenting to a VA PTSD specialty clinic. Participants used the afterdeployment.org, Post‐Traumatic Stress (PTS) Workshop, which was supplemented with brief weekly telephone calls. Half of the participants (n = 12) completed at least 5 of the 8 workshop sessions. At posttreatment, 40.0% of completers demonstrated reliable reductions on PTSD symptoms and overall d = 1.04. Treatment satisfaction and acceptability was generally positive based on Likert ratings. This web‐based intervention for PTS appears to be a feasible and potentially helpful intervention for veterans who may not otherwise receive psychosocial interventions. Given the minimal resources required and the potential reach, this web‐based intervention could be a viable addition to services provided to OEF/OIF veterans seeking PTSD specialty care. Efforts to further develop and more rigorously evaluate this approach are warranted.